THE EFFECT OF EMPIRICAL VS CULTURE-BASED THERAPY ON PATIENT OUTCOMES WITH COMPLICATED INTRA-ABDOMINAL INFECTION AT KHYBER TEACHING HOSPITAL PESHAWAR - Rubina Yaseen; Qaviullah Mian; Asad Farooq; Ajmal Khan; Muhammad Naeem; Mushtaq Ahmad (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Intra-abdominal infections are peritoneal inflammation in response to microorganisms, resulting in pus formation in the peritoneal cavity. Intra-abdominal infections are of two types: uncomplicated and complicated based on the severity of the infection. To compare the efficacy of empirical and culture-based therapy in a patient with complicated intra-abdominal infections presenting to Khyber Teaching Hospital Peshawar, a total of 694 patients of both genders with complicated intra-abdominal infections were included in the study. A sample size of 347 patients was calculated for the culture-based therapy group or Group A while 347 sample size for the empirical therapy group or Group B. Efficacy was noted after the 14th day for both groups. The age range in this study was 15 to 65 years with a mean age of 31.204±10.96 years, a mean duration of disease 55.659±18.27 hours, and a mean weight of 71.400±11.72 Kg in Group A. The mean age of the patients in Group B was 29.953±9.79 years, the mean duration of disease was 56.005 ± 18.19 hours and the mean weight was 70.308±10.81 Kg in Group B. Efficacy was observed in 310 (89.3%) patients in group A as compared to 296 (85.3%) patients in group B (P= 0.110). Our study showed that Moxifloxacin monotherapy was as well tolerated and effective as culture-based therapy in the treatment of patients with complicated intra-abdominal infections